Watch and See Strategy in Selected Neuroblastoma Case Scenarios: Success and Limitations. Issue 6 (August 2019) - Fawzy, Mohamed; El Zomor, Hossam; El Menawi, Salma; Elkinaai, Naglaa; Ahmed, Gehad; Refaat, Amal; Elahmadawy, Mai; Zaghloul, Mohamed
Abstract : Neuroblastoma (NBL) in infants has the potential to regress/mature spontaneously. The literature showed some cases, subjected to initial observation, with reasonable outcome. Deferring/avoiding active treatment was investigated in selected favorable NBL cases. Patients enrolled on the watch and see strategy (W&S) had small primary tumor, localized stages 1 to 2, uncomplicated stage 4s, or stage 3. Tissue biopsy was not mandatory for infants below 6 months with localized mass. On progression, active intervention was indicated according to disease stage and risk after biological characterization. In total, 32 patients were enrolled on W&S strategy; male/female:2.6/1. Twelve had stages 1 to 2, 16 had stage 4s, and 4 were stage 3. Primary adrenal site was reported in 85% patients, and 65% patients had small mass (⩽5 cm). Five-year overall and event-free survival were 100% and 80.9±7%, respectively, with a 43-month median follow-up duration. Spontaneous total/near total resolution of mass occurred in 50% patients. Median time to regression was 1.7 months, and 20.7 months until resolution. Only 19% patients witnessed progression; median time to progression was 4.8 months. W&S is a reasonable approach for localized and uncomplicated stages 3 and 4S NBL. Extended tumor size is a newly investigated entity in the present study. All progressive cases were safely rescued with 100% survival outcome.